2016
DOI: 10.3390/app6010012
|View full text |Cite
|
Sign up to set email alerts
|

Lamb Wave Interaction with Adhesively Bonded Stiffeners and Disbonds Using 3D Vibrometry

Abstract: There are many advantages to adhesively bonding stiffeners onto aircraft structures rather than using traditional mechanical fastening methods. However there is a lack of confidence of the structural integrity of adhesively bonded joints over time. Acousto-ultrasonic Lamb waves have shown great potential in structural health monitoring applications in both metallic and composite structures. This paper presents an experimental investigation of the use of acousto-ultrasonic Lamb waves for the monitoring of adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…The vibration energy distribution is the basis for a simple but very efficient technique that utilizes the calculation of a root mean square (RMS). Recently, the RMS has been successfully used to detect defects in aluminium plates [14][15][16], delamination in a composite T-joint [17], disbonds in a stiffened panel [18], notches and corrosion areas in aluminium plates [19], disbond inserts in composite elements [20] and voids in adhesive joints [7]. The root mean square for a continuous signal s(t) is calculated with respect to the formula:…”
Section: Root Mean Squarementioning
confidence: 99%
“…The vibration energy distribution is the basis for a simple but very efficient technique that utilizes the calculation of a root mean square (RMS). Recently, the RMS has been successfully used to detect defects in aluminium plates [14][15][16], delamination in a composite T-joint [17], disbonds in a stiffened panel [18], notches and corrosion areas in aluminium plates [19], disbond inserts in composite elements [20] and voids in adhesive joints [7]. The root mean square for a continuous signal s(t) is calculated with respect to the formula:…”
Section: Root Mean Squarementioning
confidence: 99%
“…This method was improved to be more applicable for damage detection by defining the weighted root mean square (WRMS) method [30]. Recently, the RMS has been successfully used in various damage detection applications [25,26,[31][32][33][34][35][36].Żak et al [30] investigated aluminum and composite plates as well as composite elements of a helicopter, all with the damage being simulated by an additional mass. They concluded that better resolution in WRMS maps corresponded to higher values of the weighting factor (linear or square).…”
Section: Introductionmentioning
confidence: 99%
“…Detection of delamination in a composite T-joint using RMS images was studied by Geetha et al [34]. Marks et al [35] presented experimental investigations on the detection of disbonds in a stiffened panel based on the RMS plots. Wave packets with three different frequencies, namely 100 kHz, 250 kHz, and 300 kHz, were applied.…”
Section: Introductionmentioning
confidence: 99%
“…Lamb waves are dispersive and multimodal [9]. Moreover, the propagating Lamb waves may include incident, reflected, and converted waves when they encounter a sudden thickness variation [10,11], such as circular flat bottom holes and rectangular grooves. Obviously, various wave modes make the interpretation of Lamb waves very difficult [12].…”
Section: Introductionmentioning
confidence: 99%